POSSIBILITIES OF MARKETING STRATEGY IMPLEMENTATION IN INDUSTRIAL ENTERPRISES PRODUCING CLEANING TOOLS (Marketing Journal, 2025)
This article explores the implementation potential of omnichannel marketing strategy in industrial enterprises producing cleaning products. The study is based on the POP, UTAUT2, and 3D Omnichannel models, focusing on customer experience, technology adopti on, and channel integration. The analysis confirms the effectiveness of the omnichannel approach in enhancing service quality, customer loyalty, and sales performance, and provides practical recommendations.
Keywords: omnichannel marketing; customer experience; POP model; UTAUT2; 3D model; digital strategy; industrial marketing